Analysis of English Loanwords Ayat-Ayat Cinta 2 Novel - Megah, Suswanto Ismadi (ANGLO-SAXON: Jurnal Ilmiah Program Studi Pendidikan Bahasa Inggris, 2017)
This study is aimed to analyze the novel Ayat-ayat Cinta 2 which was written by Habibirahman El-Shirazy. This study analyzed the usage of English loanwords in the novel, particularly English phrase in the novel. The data analyzed based the descriptive qualitative research based the the text of the novel. The data found of the  novel Ayat-ayat Cinta 2 is 19 data, which consist of the adjective +noun is 4 data. The Noun + noun is 12, and the Noun + adjective is 3. So, the data is mostly dominated the noun + noun. This study concluded that the usage of the  English loanwords of the novel have meaning that to make conversation more easy, and the other reason is too difficult to find equal meaning in Indonesian language. In addition, English loanwords also shows a social status as the intellectual person who always used international, particularly English in his communication.             Keywords: English,  phrases, loanwords, and novel